Depressive symptoms among Mexican adolescent girls in relation to iron status, anaemia, body weight and pubertal status: results from a latent class analysis. Issue 2 (18th May 2022) - Zarate-Ortiz, Arli Guadalupe; Verhoef, Hans; Melse-Boonstra, Alida; Woods, Bo-Jane; Lee-Bazaldúa, Elida Estefania; Feskens, Edith JM; Quiroga-Garza, Angelica; Cepeda-Lopez, Ana Carla
Abstract: Objective: The study examined the association between depressive symptoms and iron status, anaemia, body weight and pubertal status among Mexican adolescent girls. Design: In this cross-sectional study, depressive symptoms were assessed by the 6-item Kutcher Adolescent Depression Scale, and latent class analysis (LCA) was used to identify and characterise groups of girls based on depressive symptoms. Iron status and inflammation were assessed using ferritin and soluble transferrin receptor, C-reactive protein and alpha-1-acid glycoprotein, respectively. Multiple logistic and linear regressions were applied to model class membership as a function of iron status, anaemia, body weight and pubertal status. Participants: We collected data from 408 girls aged 12–20 years. Setting: Public schools in northern Mexico. Results: LCA yielded three classes of depressive symptoms: 44·4 % of the adolescents were 'unlikely to be depressed', 41·5 % were 'likely to be depressed' and 14·1 % were 'highly likely to be depressed'. Our analyses demonstrated that iron-deficient girls had greater odds of being 'likely depressed' (OR 2·01, 95 % CI 1·01, 3·00) or 'highly likely depressed' (OR 2·80, 95 % CI 1·76, 3·84). Linear regression analyses revealed that lower Hb concentrations and higher body weight increased the probability of being 'likely depressed'. There was no evidence that depressive symptoms were associated with age at menarche and years since menstruation. Conclusions: This study shows that iron-deficient adolescent girls are more likely to suffer from depressive symptoms and that lower concentrations of Hb and higher body weight increased the probability of experiencing depressive symptoms.